DEVELOPING VOCABULARY IN LEARNING SPEAKING ENGLISH OF USAHA JASA WISATA DEPARTEMENT THROUGH AUSSIE SLANG VOCABULARY BOOK AT LKP ALOHA EDU TEGALDLIMO IN G-LAND BOBBY’S SURF CAMP BANYUWANGI IN ACADEMIC YEAR 2021/2022 - Rozaq, Ridwan; Rozaq, Wahid Abdul Rozaq (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2023)
This study aims to develop learning media and improve the speaking quality of students in the LKp Aloha edu tourism service business class (usaha jasa wisata class), they always have problems when meeting Australian guests, because they have styles, language vocabs that are quite different from English which has been standardized by the international community. This product, which is in the form of an Aussie slang vocabulary book, has known the feasibility of the media so that it has produced a valid and effective media. The data collection technique in this study was to use a research and development questionnaire to produce appropriate Aussie slang vocabulary media based on assessments from media experts material experts, design experts, English teachers/tutors and responses from students. This research uses research and development (R&D) methods. The development procedure follows the Borg and Gall procedure which generally can be carried out by involving 10 main steps, namely: 1) research and information collecting, 2) planning data, 3) developing preliminary from product, 4) preliminary field testing, 5) main product revision, 6) main field testing, 7) operational product revision, 8) operational field testing, 9) final product revision, 10) Dimensions and implementation. then for research conducted in the scope of undergraduate, the research is limited to five stages, namely 1) research and information collecting, 2) planning, 3) developing preliminary from product, 4) preliminary field testing, 5) main product revision.The results of the assessment in the first question indicate that the English vocabulary card media has a very good feasibility according to media experts getting a percentage of 96%, material experts 100%, , teacher assessments 97,75% and student responses 91,23% which means this Learning Media is "Very Appropriate" to use. Keywords: Developing, Speaking Skill, Improve, Australian slang vocabulary